50 lat Wydziału Biologii Uniwersytetu Warszawskiego we wspomnieniach / - Jagielski, Tomasz (Wydawnictwo Uniwersytetu Warszawskiego, 2019)
A commemorative publication recounting the history of the Faculty of Biology of the University of Warsaw through the words of its former and current staff and friends. Comprised of written down interviews and split by themes into over a dozen chapters, it portrays the history of the Faculty in chronological order. It is supplemented by a collection of almost two hundred photographs from over half a century of the institution’s functioning.
https://doi.org/10.31338/uw.9788323538431
Keywords: Diaries; European diaries